The power of uptake: Responses to claims to power on anonymous online fora - Deamer, Felicity; Wolf, Michaela; Davies, Robert; Grant, Tim (Language and Law / Linguagem e Direito, 2025)
Motivated by the need to better understand criminal online spaces, earlier work enabled us to identify powerful individuals on online anonymous fora as those who draw on multiple power resources in their interactions, and to show how power operates differently across three different fora; a general discussion forum, a white nationalist forum, and a Dark Web CSEA forum (Newsome-Chandler and Grant 2024). This previous work focused on how users make claims to power in order to direct or influence the beliefs or behaviour of others. Here we explore the same three datasets (a sample of 24 threads from each forum), but we have shifted our focus to the other side of the interaction; onto those who are liable to be influenced or persuaded by claims to power. The objective is to provide a small-scale analysis of the effects of claims to power on recipients – to create a pragmatics-based descriptive taxonomy of their responses to claims to power. Using a purpose specific speech act coding framework, we have devised a taxonomy of response types that can hopefully be scaled through automation to determine how influence, persuasion, and potentially radicalisation work within distinct anonymous online networks, and to potentially pick out individuals who may be more vulnerable to persuasion and influence.